Recent Advances in Gestational Diabetes Mellitus - Benhalima, Katrien (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The papers included in this issue vary from research on pregnancy outcomes to screening and diagnosis of GDM, the use of new biomarkers, and the evaluation of long-term metabolic risk and intervention strategies postpartum in mothers and offspring.